Bone Fragment of Early Neolithic ruminants from the Archaeological Site Vučedol (Vukovar, Croatia) - Mihelić, Damir (Array, 1997)
During excavations of Starčevo culture early neolithic layer of Vučedol site in 1985. Among numerous findings of shells (Unionidae) and snails (Helicidae) paucity of animal bone fragments were found.We compared excavated osteological materials with recent ones of domesticated ruminants from osteological collection of Department of Anatomy, Histology and Embriology (Faculty of Veterinary Medicine, Zagreb). osteological remains can be separated of fragments of feral (wild cattle, red deer, roe deer) and domesticated animals /cattle, sheep, goat) species. The most frequent species is cattle. Difference in bone fragments of cattle are so subspecies or mixed form can be distinguished. Osteological findings of other ruminants are sporadic. Such findings are of great importaints if we mention that gathering, hunting and farming have long been image of early Stone Age.